Dissolved rubidium to strontium ratio as a conservative tracer for wastewater effluent-sourced contaminant inputs near a major urban wastewater treatment plant. (15th October 2021) - Smith, Joseph P.; Boyd, Thomas J.; Cragan, Jennifer; Ward, Matthew C.
Highlights: ● Rb/Sr ratio enriched in MWW effluent as compared to Potomac River surface waters. ● Rb/Sr ratio correlated to dissolved Gd in Potomac River surface waters. ● Can use Rb/Sr ratio to estimate MWW contributions to Potomac River surface waters. ● Rb/Sr ratio is simple and cost-effective conservative MWW indicator and tracer. Abstract: Municipal wastewater (MWW) effluent discharges can introduce contaminants to receiving waters which may have adverse impacts on local ecosystems and human health. Conservative chemical constituents specific to the MWW effluent stream can be used to quantify and trace wastewater effluent-sourced contaminant inputs. Gadolinium (Gd), a rare earth element used as a contrasting agent in medical magnetic resonance imaging, can be found in urban MWW streams. Dissolved anthropogenic Gd has been shown to be an indicator and potential conservative tracer for MWW effluent in receiving waters. Like other known MWW tracers, it can be difficult and expensive to measure. Dissolved rubidium (Rb) to strontium (Sr) ratio enrichment in biological materials such as blood and urine can lead to enriched Rb/Sr values in MWW effluent relative to natural waters. This ratio is relatively easy and inexpensive to measure and represents a promising additional indicator for MWW effluent in receiving waters in urbanized freshwater systems. In July 2015 and 2016 surface water samples were collected from sites in the tidal-fresh Potomac River in the vicinity of the Blue Plains Advanced Wastewater Treatment Plant (BPAWWTP) outfall near Washington, DC USA along with treated MWW effluent samples from the BPAWWTP. Dissolved Rb/Sr ratios were measured in these waters and compared to dissolved Gd concentrations in order to demonstrate the potential of the dissolved Rb/Sr ratio as a conservative indicator for MWW effluent. Results suggest the dissolved Rb/Sr ratio represents a simple and cost-effective indicator and conservative tracer for MWW effluent. It can be used with, or in place of, other proven tracers to investigate wastewater impacts in highly-urbanized, anthropogenically-impacted freshwater systems like the tidal fresh Potomac River and perhaps in a wider range of geologic settings than previously thought. A case study is presented as an example to demonstrate the potential of using dissolved Rb/Sr ratios to trace MWW-sourced nutrient inputs from a major WWTP like BPAWWTP to the receiving waters of tidal-fresh Potomac River. Graphical abstarct: Image, graphical abstract